Further study on the labial palp in the Isotomidae (Collembola) with reference to the genus Heteroisotoma Stach - Jie, Ding; Potapov, Mikhail; Sokolova, Elena (Zootaxa, 2011)
Two new species of the genus Heteroisotoma Stach are described from Northeast China, North Korea, and Far East of Russia. They are typical members of the genus although sharing spines on the dens with the genus Semicerura Maynard. In all members of Heteroisotoma, three additional processes on the labial palp are discovered and proposed as a new diagnostic generic character. The genus Heteroisotoma is rediagnosed and a key and records of known species are given. A contribution is made to the knowledge of labial palp.